Fossil coniferous wood from the Early Cretaceous Jehol Biota in western Liaoning, NE China: New material and palaeoclimate implications. (June 2016) - Ding, Qiuhong; Tian, Ning; Wang, Yongdong; Jiang, Zikun; Chen, Shuwang; Wang, Dong; Zhang, Wu; Zheng, Shaolin; Xie, Aowei; Zhang, Guoqiang; Liu, Zhongjian
Abstract: The Early Cretaceous Jehol Biota, one of the most important Mesozoic lagerstätten in East Asia, is especially well-known for occurrences of fossil feathered dinosaurs and early angiosperms. However, the terrestrial biodiversity, especially the fossil wood record, is poorly known. In this study, several structurally preserved coniferous wood specimens from the Lower Cretaceous Yixian Formation are investigated, based on collections from the Heichengzi Basin in Beipiao of western Liaoning, Northeast China. Four species referred to four genera of fossil wood are described, including Taxodioxylon heichengziense sp. nov., Thujoxylon beipiaoense sp. nov., Sciadopityoxylon liaoningense Ding and Protocedroxylon shengjinbeigouense sp. nov. These new records enlarge the fossil wood diversity of the Yixian Formation up to 10 species in 9 genera, and provide further insights into the forest vegetation composition of the Early Cretaceous Jehol Biota. Systematic analysis of the floral constitution indicates that the petrified forests of the Yixian Formation are dominated by conifers, represented by Araucariaceae, Podocarpaceae, Sciadopityaceae, Pinaceae and Cupressaceae in the western Liaoning region. Palaeoclimatical analysis of the fossil wood assemblage implies that the western Liaoning region was dominated by a cool temperate, wet and seasonal climate with variable interannual water supply in the western Liaoning region during the Early Cretaceous. Highlights: Several new coniferous wood taxa are described from the Yixian Formation (K1 ) in Beipiao of western Liaoning, NE China. These new findings contribute to a better understanding of floral composition of the Early Cretaceous Jehol Biota. Fossil wood assemblage indicates a cool temperate wet and seasonal climate in western Liaoning during the Early Cretaceous.